PENGARUH WAKTU PENETAPAN ANGGARAN DAN FISCAL STRESS TERHADAP SERAPAN ANGGARAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI ACEH - Imam Hanif; suparno Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this study is to examine the effect of budget approval punctuality and fiscal stress to the budget absorption of the local governments in Aceh. The objects of this study are all the governments of districts and cities in Aceh (18 districts and 5 cities).The method used in this study is hypothetical testing. The data used in this study is secondary data obtained from Dinas Keuangan Aceh (DKA). The population in this study are all the governments of every districts and cities in Aceh for 3 years of observation (2013-2015). Data analyses method used in this study is multiple linear regression.The results of this study are either partially or simultaneously support the hypothesis that budget approval punctuality and fiscal stress affect the budget absorption of the governments of districts and cities in Aceh